Risk Factors for Failure of Direct Restorations in General Dental Practices. (August 2020) - Wierichs, R.J.; Kramer, E.J.; Meyer-Lueckel, H.
The aim of this retrospective noninterventional multicenter practice-based study was to analyze factors influencing the survival of direct restorations. Records from patients who visited 5 private practices regularly were searched for the presence of direct restorations. Data were recorded from 7, 858 patients with 27, 407 direct restorations being detected at least 6 mo before the last recall visit. Multilevel Cox proportional hazard models were used to evaluate the association between clinical factors and time until failure. Within 228 mo, 5, 493 failures could be observed. Median survival time was 207 mo. The annual failure rates were 3.8%, 4.0%, 4.6%, 4.9%, and 3.9% for class I, II, III, IV, and V restorations, respectively. Class II and IV restorations showed a 1.1-times (95% CI, 1.0 to 1.2) and 1.2-times (95% CI, 1.1 to 1.2) higher failure rate than class I restorations ( P ≤ 0.029). Patients aged <20 y and >60 y showed up to a 1.4-times higher failure rate than patients aged 20 to 60 y ( P ≤ 0.015). Restorations that underwent check-up twice a year or more showed a significantly higher failure rate than those that did so less than twice a year ( P < 0.001). Furthermore, the dentists significantly influenced time until failure ( P < 0.001). Regarding the restorative material, composites showed up to a 2.1-times longer time until failure than GIC ( P ≤ 0.020). Moderate failure rates were observed for direct restorations in the private practice setting after up to 18.5 y. Within the limitations of the present study, several factors on the levels of practice (i.e., dentist), patient (i.e., age), and tooth (i.e., restorative material, restored surfaces according to the classification of Black) were significant predictors for the failure rate. Therefore, treatment decision should take into account most relevant factors (German Clinical Trials Register DRKS00015228).